1997
DOI: 10.1038/sj.bmt.1701012
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of pure red cell aplasia after major ABO-incompatible T cell-depleted bone marrow transplantation with erythropoietin

Abstract: Summary:Case reportA 40-year-old female with AML (FAB-M 4 ) in first CR A 40-year-old woman with acute myeloid leukemia in first remission developed pure red cell aplasia after a T underwent a T cell-depleted allogeneic BMT in October 1995. The donor was an HLA-compatible sister who was cell-depleted ABO-incompatible bone marrow transplant from her HLA-identical sister. She remained blood group 0+, while the recipient was A+. CY (60 mg/kg × 2 days) and hyperfractionated TBI (13.5 Gy transfusion-dependent for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…22 The drop will be faster after unrelated donor transplantation. 36 Attempts to hasten red cell recovery have involved plasmapheresis or immunoadsorption in an attempt to reduce isoagglutinin titers, 10,12 erythropoietin to enhance red cell production, 10,37,38 and immunosuppression with glucocorticoids or anti-thymocyte globulin. 39 The value of these maneuvers is open to question.…”
Section: Major Red Cell Incompatibilitymentioning
confidence: 99%
“…22 The drop will be faster after unrelated donor transplantation. 36 Attempts to hasten red cell recovery have involved plasmapheresis or immunoadsorption in an attempt to reduce isoagglutinin titers, 10,12 erythropoietin to enhance red cell production, 10,37,38 and immunosuppression with glucocorticoids or anti-thymocyte globulin. 39 The value of these maneuvers is open to question.…”
Section: Major Red Cell Incompatibilitymentioning
confidence: 99%
“…Major ABO-incompatible HSCT recipients may experience delayed red cell recovery after transplantation because of persistent host isohemagglutinins that suppress donor's red cell hematopoiesis. 6 Several methods have been used for treatment of this complication: removal of ABO antibodies by large-volume plasmapheresis prior or after transplantation, 7 transfusion of donor-type red cells, 8 removal of anti-A and anti-B antibodies by immunoadsorption on immobilized blood group antigens, 9 erythropoietin (EPO) to enhance red cell production, 10 immunosuppression with glucocorticoids or antithymocyte globulin and treatment with rituximab. 11 Removal of immunoglobulins with Ig-Therasorb s immunoadsorption is a novel method for the treatment of various hematologic and immunologic diseases, such as acquired coagulation factor inhibitors, dilated cardiomyopathy and the removal of anti-HLA antibodies prior to renal transplantation.…”
mentioning
confidence: 99%
“…2 In our patient, in vitro studies revealed that the patient's fresh serum inhibited normal marrow erythroid colony formation, suggesting a complement-dependent inhibition of erythroid progenitor cells. In addition, cytogenetic data documented a progressive graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…4 A wellrecognized mechanism of PRCA complicating major ABOincompatible BMT involves antibodies towards red cell precursors; 2 a T cell-mediated suppression of erythropoiesis has also been described. 2 ABO-incompatible BMT is a difficult task; various immunosuppressive regimens, erythropoietin and plasmapheresis have been used with variable results. 2 Immunemediated mechanisms may also play a key role in the development of late graft failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation